2014
DOI: 10.1021/jm500690j
|View full text |Cite
|
Sign up to set email alerts
|

Tailor-Made Fluorescent Trilobolide To Study Its Biological Relevance

Abstract: Trilobolide (Tb) is a potent natural counterpart of thapsigargin, which has shown promising results in cancer clinical trials. Here, we report a rational approach to study intracellular localization and biological activity of this sesquiterpene lactone. We conjugated Tb with a green-emitting Bodipy dye attached by alternative linkers of different lengths. The live-cell imaging of the prepared bioconjugates brought clear evidence that Tb-Bodipy localized in the endoplasmic reticulum (ER) of various cancer cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 29 publications
4
15
0
Order By: Relevance
“…First, we analyzed the rate of cell uptake of compound 5 in U-2 OS ( which is in agreement with the site of localization of another SL, a SERCA inhibitor, trilobolide [3]. However, we observed partial co-localization also in mitochondria, in which SERCA is not present.…”
Section: Intracellular Localization Of Archangelolide-dansyl Conjugatesupporting
confidence: 66%
See 2 more Smart Citations
“…First, we analyzed the rate of cell uptake of compound 5 in U-2 OS ( which is in agreement with the site of localization of another SL, a SERCA inhibitor, trilobolide [3]. However, we observed partial co-localization also in mitochondria, in which SERCA is not present.…”
Section: Intracellular Localization Of Archangelolide-dansyl Conjugatesupporting
confidence: 66%
“…Trilobolide exhibits strong induction of nitric oxide (NO) in eukaryotic cells, which in turn evokes synthesis of IL-6, INF-γ and TNF-α. Furthermore, trilobolide has very similar structure to the well-described SL thapsigargin and was found cytotoxic [3] due to acting by the same mechanism in cells [4]. It was, however, found that trilobolide may be modified in such a way that its cytotoxicity is reduced while the immuno-biological properties are retained [5].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…1 ) is a potent natural compound of the sesquiterpene lactone class, which causes cell death via depleting intracellular Ca 2+ ion stores by the irreversible inhibition of sarco-/endoplasmic reticulum Ca 2+ -ATPase (SERCA) already at nanomolar concentrations [ 27 30 ]. In our recent study, we reported the localization of fluorescent Tb-BODIPY conjugates in the endoplasmic reticulum of a number of cancer cell lines [ 31 ]. Besides that, Tb is of high interest also for the fact that it induces high production of nitric monoxide (NO) which has an immunomodulating effect on rat peritoneal cells [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides that, Tb is of high interest also for the fact that it induces high production of nitric monoxide (NO) which has an immunomodulating effect on rat peritoneal cells [ 32 ]. We documented in [ 31 ] that Tb, prepared as a fluorescent conjugate with green-emitting BODIPY, induced a dose-dependent NO production in primary rat macrophages. The potency of the fluorescent Tb to express inducible NO and cytokine secretion was shifted to a low micromolar range in comparison to the submicromolar activity of Tb itself.…”
Section: Introductionmentioning
confidence: 99%